Modelli di valutazione di un sistema scolastico inclusivo Prospettive di dialogo tra implementazione, ricerca e (auto-) miglioramento - Dell'Anna, Silvia (Traiettorie inclusive, 2021)
In the last two decades, the topic of evaluation of the quality of educational systems has become central in the national and international arena. Evaluation is seen as a tool to verify the effectiveness and sustainability of the systems with the aim of improvement. In the Italian context, inclusion is a key principle of the school system, at all levels of education and encompasses various factors: from nursery school to university, from classroom teaching to school organisation and policies. For this reason, the evaluation of the school system cannot be separated from that of inclusive education. This book presents an overview of current evaluation systems and the state of implementation and research on school inclusion. The analysis highlights the multiple interconnections between the general evaluation of the school system and the evaluation of school inclusion, and aims to unify them through a new and original ecological approach that promotes a recursive and generative link between practice, research and evaluation. The book is addressed to researchers working in the field of educational evaluation and school inclusion, as well as teachers, principals and other education professionals who seek a collaborative, participatory and transformative evaluation system.